Procedural Justice in Selection from the Lens of Psychological Contract Theory - Huy Phuong Tran; Vu Ngan Hoang; Hoang Hue Thi; Nguyen Hanh Thi Hai (Organizacija, 2020)
Background and purpose: In recruitment and selection, job applicants do not only base their justice judgment on the actual experience but also compare what happens and what they expect. This study, therefore, investigates applicants’ reaction to procedural justice in recruitment selection through the lens of psychological contract framework. Psychological contract theory highlights the role of expectations, discrepancies between perception and expectation, and perceived contract breach on individual outcomes.